Doped and undoped graphene platforms: the influence of structural properties on the detection of polyphenols - Chng, Chu'Er; Sofer, Zdenek; Pumera, Martin; Bonanni, Alessandra (Scientific reports, 2016)
There is a huge interest in doped graphene and how doping can tune the material properties for the specific application. It was recently demonstrated that the effect of doping can have different influence on the electrochemical detection of electroactive probes, depending on the analysed probe, on the structural characteristics of the graphene materials and on the type and amount of heteroatom used for the doping. In this work we wanted to investigate the effect of doping on graphene materials used as platform for the detection of catechin, a standard probe which is commonly used for the measurement of polyphenols in food and beverages. To this aim we compared undoped graphene with boron-doped graphene and nitrogen doped graphene platforms for the electrochemical detection of standard catechin oxidation. Finally, the material providing the best electrochemical performance was employed for the analysis of real samples. We found that the undoped graphene, possessing lower amount of oxygen functionalities, higher density of defects and larger electroactive surface area provided the best electroanalytical performance for the determination of catechin in commercial beer samples. Our findings are important for the development of novel graphene platforms for the electrochemical assessment of food quality.
Keywords: katechin; nápoje; grafit; polyfenoly; dusík; Boron; Oxidation-Reduction; Beverages; Graphite; Polyphenols; bor; analýza potravin; Catechin; elektrochemické techniky; Electrodes; Food Analysis; Electrochemical Techniques; oxidace-redukce; elektrody; Nitrogen